Mouffe, Chantal (2019). Por um populismo de esquerda. Lisboa: Gradiva, 95 pp. ISBN 978-989-616- 906-0 - Sousa, João Carlos de (2021)
The work Por Um Populismo de Esquerda (For a Left Populism) by Chantal Mouffe is part of the long-standing neo-Marxist tradition endorsed by a vast and diverse community of readers, ranging from Sociology to Political Science and Philosophy. For the French author, it is clear that populism itself may not be solely and simply synonymous with dysfunctionality and democratic pathology. What she calls the “populist moment” is inserted in a socio-historical and cultural narrative, where different dispositions of the different social structures are metamorphosed in a permanent dialectical process of thesis, antithesis and synthesis.